Ultrasound-guided breast-sparing surgery to improve cosmetic outcomes and quality of life. A prospective multicentre randomised controlled clinical trial comparing ultrasound-guided surgery to traditional palpation-guided surgery (COBALT trial) - Bergers Elisabeth; Taets van Amerongen Annette HM; Bosch Anne; de Roos Wilfred K; de Widt Louise; Poortman Pieter; Muller Sandra; van der Veen Henk; Rijna Herman; Lopes Cardozo Alexander MF; Schreurs Hermien WH; Zonderhuis Barbara M; et al. (BMC Surgery, 2011)
Abstract Background Breast-conserving surgery for breast cancer was developed as a method to preserve healthy breast tissue, thereby improving cosmetic outcomes. Thus far, the primary aim of breast-conserving surgery has been the achievement of tumour-free resection margins and prevention of local recurrence, whereas the cosmetic outcome has been considered less important. Large studies have reported poor cosmetic outcomes in 20-40% of patients after breast-conserving surgery, with the volume of the resected breast tissue being the major determinant. There is clear evidence for the efficacy of ultrasonography in the resection of nonpalpable tumours. Surgical resection of palpable breast cancer is performed with guidance by intra-operative palpation. These palpation-guided excisions often result in an unnecessarily wide resection of adjacent healthy breast tissue, while the rate of tumour-involved resection margins is still high. It is hypothesised that the use of intra-operative ultrasonography in the excision of palpable breast cancer will improve the ability to spare healthy breast tissue while maintaining or even improving the oncological margin status. The aim of this study is to compare ultrasound-guided surgery for palpable tumours with the standard palpation-guided surgery in terms of the extent of healthy breast tissue resection, the percentage of tumour-free margins, cosmetic outcomes and quality of life. Methods/design In this prospective multicentre randomised controlled clinical trial, 120 women who have been diagnosed with palpable early-stage (T1-2N0-1) primary invasive breast cancer and deemed suitable for breast-conserving surgery will be randomised between ultrasound-guided surgery and palpation-guided surgery. With this sample size, an expected 20% reduction of resected breast tissue and an 18% difference in tumour-free margins can be detected with a power of 80%. Secondary endpoints include cosmetic outcomes and quality of life. The rationale, study design and planned analyses are described. Conclusion The COBALT trial is a prospective, multicentre, randomised controlled study to assess the efficacy of ultrasound-guided breast-conserving surgery in patients with palpable early-stage primary invasive breast cancer in terms of the sparing of breast tissue, oncological margin status, cosmetic outcomes and quality of life. Trial Registration Number Netherlands Trial Register (NTR): NTR2579